2019
DOI: 10.1021/acsenergylett.9b01949
|View full text |Cite
|
Sign up to set email alerts
|

Double-Helicene-Based Hole-Transporter for Perovskite Solar Cells with 22% Efficiency and Operation Durability

Abstract: Amelioration of the mobility and, in particular, the thermal stability of a hole-transporting molecular semiconductor is a practicable strategy to attain the enhancement of both power conversion efficiency (PCE) and operational durability of perovskite solar cells (PSCs). Here a cost-effective double-[4]helicene-based molecular semiconductor (DBC-OMeDPA) is synthesized for a solution-deposited thin film, exhibiting an improved hole mobility in comparison with state-of-the-art spiro-OMeTAD control. X-ray crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…Generally, the thermal stability of organic materials will be enhanced by improving the rigidity and planarity of the conjugated system [22] . In the present work, the coplanar π‐extended quinoxaline core is found to significantly increase the thermal stability of HTMs.…”
Section: Figurementioning
confidence: 58%
See 1 more Smart Citation
“…Generally, the thermal stability of organic materials will be enhanced by improving the rigidity and planarity of the conjugated system [22] . In the present work, the coplanar π‐extended quinoxaline core is found to significantly increase the thermal stability of HTMs.…”
Section: Figurementioning
confidence: 58%
“…[19][20][21] Generally, the thermal stability of organic materials will be enhanced by improving the rigidity and planarity of the conjugated system. [22] In the present work, the coplanar pextended quinoxaline core is found to significantly increase the thermal stability of HTMs. The decomposition temperature (T d , 5 % mass loss; see Figure 1 c) for TQ4 (461 8C) is much higher than that of TQ3 (424 8C).…”
mentioning
confidence: 58%
“…It clearly can be seen that the device encapsulated by UVCA with paraffin shows superior thermal stability, which retain ≈90% of its initial efficiency after annealed under 65 °C in the ambient environment with 40–60% RH for over 1000 h. At the same time, the efficiency of the UVCA without paraffin‐encapsulated device dropped rapidly. Several previous works showed that small molecule Spiro‐OMeTAD with a low intrinsic glass transition temperature would crystallize under thermal stress . The hole transport layer (Spiro‐OMeTAD) has been modified by conductive polymer poly(triarylamine), which is effective to improve the thermal stability of the device.…”
Section: Resultsmentioning
confidence: 99%
“…used chlorobenzene antisolvent dripping to fabricate triple cation mixed halide perovskite films. [ 87 ] Utilizing antisolvent treatment and a new kind of hole transport material N 3 , N 3 , N 6 , N 6 , N 11 , N 11 , N 14 , N 14 ‐octakis(4methoxyphenyl)dibenzo[g,p]chrysene‐3,6,11,14‐tetraamine (DBC‐OMeDPA), an efficiency of 22% has been achieved. In addition, Liu et al.…”
Section: Role Of Antisolvents To Improve the Perovskite Film Formationmentioning
confidence: 99%